2013
DOI: 10.1111/iju.12192
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of the PADUA and the RENAL scoring systems for renal neoplasms: A retrospective study of 245 patients undergoing laparoscopic partial nephrectomy

Abstract: Abbreviations & AcronymsObjective: To investigate the clinical significance of preoperative aspects and dimensions used for anatomic (PADUA) and radius exophytic/endophytic nearness anterior/posterior location (RENAL) scoring systems for renal neoplasms in patients undergoing laparoscopic partial nephrectomy. Methods: A retrospective analysis was carried out on clinical data of 245 Chinese patients with renal neoplasms undergoing laparoscopic partial nephrectomy from June 2008 to June 2012. The perioperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
3
20
1
4
Order By: Relevance
“…The same group stratification was shown to be independently associated with perioperative complications. Long et al [28] [30] analysed the correlations between the two scoring systems and both WIT and perioperative complications. In their series of 245 patients treated with laparoscopic PN, they found that only the R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 99%
“…The same group stratification was shown to be independently associated with perioperative complications. Long et al [28] [30] analysed the correlations between the two scoring systems and both WIT and perioperative complications. In their series of 245 patients treated with laparoscopic PN, they found that only the R.E.N.A.L.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these systems allow a consensus in the evaluation of tumors among surgeons. [28] The evaluation of these scores showed that there is not any significant difference among the scoring systems and tumor stage or perioperative complications. [2829] Pre-operative aspects and dimensions used for an anatomical score ≥ 10 and RENAL score ≥9 are factors demonstrating a high risk for perioperative complications.…”
Section: Lpnmentioning
confidence: 99%
“…[28] The evaluation of these scores showed that there is not any significant difference among the scoring systems and tumor stage or perioperative complications. [2829] Pre-operative aspects and dimensions used for an anatomical score ≥ 10 and RENAL score ≥9 are factors demonstrating a high risk for perioperative complications. [30] An increasing RENAL score is associated with histological features of tumor aggressiveness and a greater proportion of major complications.…”
Section: Lpnmentioning
confidence: 99%
“…nephrometry and PADUA scores, have been developed to help predict the risk of surgical complications and postoperative renal function. [16][17][18][19][20][21][22] Despite these guidelines and scoring systems, a lack of consensus often exists among urologists when different treatment options are presented for the same patient. While much of the discussion may focus around patient and diseasespecific factors, a variety of surgeon-specific factors may also influence treatment decisions.…”
Section: Introductionmentioning
confidence: 99%